Linear sea-level response to abrupt ocean warming of major West Antarctic ice basin - Mengel, Matthias; Feldmann, Johannes; Levermann, Anders (Prof. Dr.) (Nature Climate Change, 2016)
Antarctica’s contribution to global sea-level rise has recently been increasing1. Whether its ice discharge will become unstable and decouple from anthropogenic forcing2,3,4 or increase linearly with the warming of the surrounding ocean is of fundamental importance5. Under unabated greenhouse-gas emissions, ocean models indicate an abrupt intrusion of warm circumpolar deep water into the cavity below West Antarctica’s Filchner–Ronne ice shelf within the next two centuries6,7. The ice basin’s retrograde bed slope would allow for an unstable ice-sheet retreat8, but the buttressing of the large ice shelf and the narrow glacier troughs tend to inhibit such instability9,10,11. It is unclear whether future ice loss will be dominated by ice instability or anthropogenic forcing. Here we show in regional and continental-scale ice-sheet simulations, which are capable of resolving unstable grounding-line retreat, that the sea-level response of the Filchner–Ronne ice basin is not dominated by ice instability and follows the strength of the forcing quasi-linearly. We find that the ice loss reduces after each pulse of projected warm water intrusion. The long-term sea-level contribution is approximately proportional to the total shelf-ice melt. Although the local instabilities might dominate the ice loss for weak oceanic warming12, we find that the upper limit of ice discharge from the region is determined by the forcing and not by the marine ice-sheet instability.